Atmospheric Turbulence : a Molecular Dynamics Perspective. - Tuck, Adrian F. (OUP Oxford, 2008)
This book focuses on the direct link between molecular dynamics and atmospheric variation, uniting molecular dynamics, turbulence theory, fluid mechanics and non equilibrium statistical mechanics. - ;This book, authored by a well-known researcher and expositor in meteorology, focuses on the direct link between molecular dynamics and atmospheric variation. Uniting molecular dynamics, turbulence theory, fluid mechanics and non equilibrium statistical mechanics, it is relevant to the fields of applied mathematics, physics and atmospheric sciences, and focuses on fluid flow and turbulence, as well.